Documentary criminology: Girl Model as a case study. (December 2017) - Redmon, David
Visual and cultural criminology are integrated with documentary filmmaking to develop a theoretically grounded, practice-based approach called 'documentary criminology'. The first section establishes the need for documentary filmmaking in criminology and outlines methodological opportunities. The second section examines theoretically the aesthetics and substance of documentary criminology. The third section takes the film Girl Model (Redmon and Sabin, 2011) as a case study to demonstrate how documentary criminology embedded in lived experience (in this case, the experience of scouts that recruit young Russian girls, purportedly for the modelling industry) can depict sensuous immediacy. The final section contrasts the aesthetic and ethical consequences of documentary criminology within Carrabine's (2012, 2014) concept of 'just' images to a documentary filmmaking approach that remains interpretively open-ended. Readers can access Girl Model athttps://vimeo.com/29694894 with the password industry .